2013
DOI: 10.1371/journal.pone.0075845
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolites Enhance Secretion Acting on SNARE Microdomains and Altering the Extent and Kinetics of Single Release Events in Bovine Adrenal Chromaffin Cells

Abstract: Lipid molecules such as arachidonic acid (AA) and sphingolipid metabolites have been implicated in modulation of neuronal and endocrine secretion. Here we compare the effects of these lipids on secretion from cultured bovine chromaffin cells. First, we demonstrate that exogenous sphingosine and AA interact with the secretory apparatus as confirmed by FRET experiments. Examination of plasma membrane SNARE microdomains and chromaffin granule dynamics using total internal reflection fluorescent microscopy (TIRFM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…In this neuroendocrine model, incubation with FTY‐720, increases the frequency of vesicle fusions during the first round of cell stimulation by depolarization but decreases the amount of vesicles recruited in subsequent stimulations, (V. Garcia‐Martinez, J. Villanueva, Y. Gimenez‐Molina & L. M. Gutiérrez, unpublished results). Furthermore, by using FRET, we have observed that FTY‐720 interacts at the molecular level with SNARE clusters in chromaffin cells as was previously described for sphingosine and AA . In addition, FTY720 could also interact with F‐actin governing the motion of the vesicles in the close proximity of secretory sites .…”
Section: Fty‐720 An Analogue Of Sphingosine Revealed Multiple Possibsupporting
confidence: 70%
See 3 more Smart Citations
“…In this neuroendocrine model, incubation with FTY‐720, increases the frequency of vesicle fusions during the first round of cell stimulation by depolarization but decreases the amount of vesicles recruited in subsequent stimulations, (V. Garcia‐Martinez, J. Villanueva, Y. Gimenez‐Molina & L. M. Gutiérrez, unpublished results). Furthermore, by using FRET, we have observed that FTY‐720 interacts at the molecular level with SNARE clusters in chromaffin cells as was previously described for sphingosine and AA . In addition, FTY720 could also interact with F‐actin governing the motion of the vesicles in the close proximity of secretory sites .…”
Section: Fty‐720 An Analogue Of Sphingosine Revealed Multiple Possibsupporting
confidence: 70%
“…Simultaneously, our group at the Institute of Neurosciences of Alicante performed experiments in adrenomedullary chromaffin cells, using the amperometry technique to detect the release of catecholamines from individual fusion events by their oxidation at the tip of a carbon fibre . In our study, sphingosine and derivatives were produced by SMase treatment of the cells, and resulted in the increase of the amount of catecholamines released in individual fusions with detection of changes in the kinetics of the process suggesting changes in the mode of fusion of the vesicles.…”
Section: Signalling Lipids Increase the Frequency And Quantal Releasementioning
confidence: 94%
See 2 more Smart Citations
“…Analysis of single granule release kinetics by amperometry shows that both sphingomyelinase and arachidonic acid treatment markedly enhance the amount of catecholamines released per individual event [88]. In comparison, another study reports that disruption of microdomains by sphingomyelinase inhibits Ca 2+ sensitivity and late kinetics of secretory vesicle fusion [89].…”
Section: Crosstalk Between Sphingolipid Glycerophospholipid and Stementioning
confidence: 99%